Business Development of Air Tebu (Sugarcane Water) in Sungai Alam Village - kartika alfira; Adrian Irnanda Pratama (Politeknik Negeri Bengkalis, 2023)
The purpose of this final project is to develop this business by creating product diversification, business branding, packaging, new booths, logos, Standard Operating Procedures (SOP), marketing mix, constraints and solutions encountered during the implementation of this final project to increasing income. This final project uses 3 methods consisting of a project preparation plan, project implementation plan and project accomplishment plan. The results of the implementation of this final project are diversified products in the form of Kasturi Sugarcane and Ginger Sugarcane, a business brand in the form of